A study on antimicrobial agents utilization pattern using anatomical therapeutic chemical / daily defined dose system and adverse drug reaction pattern in the intensive care unit of a tertiary care teaching hospital in North Eastern state of India - Ray, Debasis; Datta, Smita (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Successful use of antibiotics has brought a revolutionary change in the management of infectious diseases but has also resulted in its irrational use. Indiscriminate use of anti-microbial agents (AMAs) has been well-documented in the ICUs where polypharmacy is a common phenomenon, thus increasing the risk of Adverse Drug Reactions (ADRs). It is extremely imperative to evaluate the prescribing pattern of antimicrobials for enabling suitable modifications in prescribing patterns; to increase the therapeutic benefits and for optimizing the health care services. Methods: With the objective to assess the prescription patterns of AMAs and the rationality of their use this observational study was undertaken in the Intensive Care Unit of a Tertiary Care Hospital for two months. Results: Of the total 127 patients, 80 (62.99%) were male and 47 (37.01%) were female at an average age of 51.3±18.3 years. 102 (80.31%) patients received AMAs at average of 1.71±0.99 and 25 (19.69%) didn’t. Betalactam antibiotics were the most frequently (72.99 %) prescribed class. Meropenem was the most commonly prescribed (41 occasions) agent. The length of stay in ICU per patient was 4.42±3.49 days. 41.63% patients had more than two morbidities. No AMAs were prescribed in generic name. In 28 (27.45%) patients the AMAs prescribing were irrational. Conclusions: The high utilization rates of costly AMAs and irrational prescriptions are matters of great concern and need to be urgently addressed by use of guidelines, surveillance and antibiotic restriction policies and sensitization programs at all level of healthcare.